1984
DOI: 10.1002/bjs.1800710105
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence following ‘curative’ surgery for large bowel cancer: II. The rectum and rectosigmoid

Abstract: 1988 patients with an adenocarcinoma of the rectum (1292; 65 per cent) or rectosigmoid (696; 35 per cent) have been studied. A resection (1700 patients) or polypectomy (124 patients) was performed in 1824 (92 per cent) and, of the former, 1376 patients either underwent abdominoperineal (AP) excision of the rectum (788 patients) or an anterior resection (598 patients). The in-hospital mortality was 63 patients (8 per cent) for AP and 44 (7 per cent) for anterior resection, and a curative resection had been perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1
6

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(78 citation statements)
references
References 16 publications
4
67
1
6
Order By: Relevance
“…The increased AL rate may be related to the number of highrisk low rectal anastomoses [38]. Conversely our in-hospital mortality of 2.3% is in the lower range compared to a multicentre studies from Germany (2.7-3.1%) [31,39], Sweden (1-4% ) [28], Norway (3.0%) [33] and United Kingdom (7%) [25].We found that hospital case volume correlated with a lower incidence of AL. Others have found that higher surgeon case volume is associated with lower rates of morbidity regardless of the hospital case volume [28,32,40].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The increased AL rate may be related to the number of highrisk low rectal anastomoses [38]. Conversely our in-hospital mortality of 2.3% is in the lower range compared to a multicentre studies from Germany (2.7-3.1%) [31,39], Sweden (1-4% ) [28], Norway (3.0%) [33] and United Kingdom (7%) [25].We found that hospital case volume correlated with a lower incidence of AL. Others have found that higher surgeon case volume is associated with lower rates of morbidity regardless of the hospital case volume [28,32,40].…”
mentioning
confidence: 67%
“…Only a minority of studies are nationwide multi-institutional surveys [31][32][33]. Comparison of complication rates between series is difficult because of the different referral patterns and different study periods, and because relatively few studies distinguish between colon and rectal site, since the incidence of AL is higher after rectal cancer surgery [5,25].The aim of this study was to assess the incidence and gravity of AL after surgery for rectal cancer performed by Italian colorectal surgeons, and to identify factors predicting the incidence and gravity of AL in this patient population. …”
mentioning
confidence: 99%
“…[1][2][3] Although the use of adjunctive preoperative or postoperative chemotherapy/radiation therapy has reduced considerably the incidence of local recurrence, approximately 10 -15% of patients still develop recurrence of the disease in the pelvis. 4,5 Salvage surgery for the recurrent carcinoma is rarely successful.…”
mentioning
confidence: 99%
“…With regard to the pattern of recurrence, some reports have stated that tumor perforation was associated with highly local and peritoneal recurrence similar to hematogenous recurrence (10,14,15), whereas the pattern of recurrence in oral perforation has been infrequently reported. In the present study, the rate of recurrence was 39% (7/17) in group A and 29% (6/18) in group B.…”
Section: Discussionmentioning
confidence: 99%